The complete chloroplast genomes of two Wisteria species, W. floribunda and W. sinensis (Fabaceae). (1st November 2016) - Kim, Na-Rae; Kim, Kyunghee; Lee, Sang-Choon; Lee, Jung-Hoon; Cho, Seong-Hyun; Yu, Yeisoo; Kim, Young-Dong; Yang, Tae-Jin
Abstract: Wisteria floribunda and Wisteria sinensis are ornamental woody vines in the Fabaceae. The complete chloroplast genome sequences of the two species were generated by de novo assembly using whole genome next generation sequences. The chloroplast genomes of W. floribunda and W. sinensis were 130 960 bp and 130 561 bp long, respectively, and showed inverted repeat (IR)-lacking structures as those reported in IRLC in the Fabaceae. The chloroplast genomes of both species contained same number of protein-coding sequences (77), tRNA genes (30), and rRNA genes (4). The phylogenetic analysis with the reported chloroplast genomes confirmed close taxonomical relationship of W. floribunda and W. sinensis .